Model Konsumsi Yang Bertanggungjawab Perspektif Alquran dan Hadis - Ferdi Dermawan Nasution; Rahmi Syahriza (CV. PUSDIKRA MITRA JAYA, 2026)
The current consumption model of Muslim society has transformed from mere regulatory compliance to a complex ethical lifestyle, marked by the phenomenon of